1923
DOI: 10.1084/jem.38.4.419
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic Growth Principles of Serum and Their Relation to Old Age

Abstract: It may be concluded that, under the conditions of the experiments: 1. The inhibiting action on homologous fibroblasts of the heated serum of a young animal increases relatively more than that of an old animal. After it has been heated, the inhibiting action of the serum of the old animal is still greater than that of the young animal. 2. The CO2 precipitate obtained from the serum of a young animal definitely increases the proliferative activity of homologous fibroblasts, while th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

1925
1925
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(10 citation statements)
references
References 0 publications
0
9
0
1
Order By: Relevance
“…So far, it is evident that there is at least one growth promoting factor in the euglobulin fraction of cord serum. This factor would seem to correspond to the growth-promoting factor described by Baker and Carrel (6) and Carrel and Ebeling (7) in the euglobulin fraction of chicken serum and perhaps to the protein fraction isolated from sheep heart by Hoff man, Dingwall, and Andrus (8).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…So far, it is evident that there is at least one growth promoting factor in the euglobulin fraction of cord serum. This factor would seem to correspond to the growth-promoting factor described by Baker and Carrel (6) and Carrel and Ebeling (7) in the euglobulin fraction of chicken serum and perhaps to the protein fraction isolated from sheep heart by Hoff man, Dingwall, and Andrus (8).…”
Section: Discussionmentioning
confidence: 55%
“…Growth-promoting fractions have been obtained from adult tissue extracts and serum as well as embryonic tissues. Baker and Carrel (6) and Carrel and Ebeling (7) isolated a euglobulin fraction from chicken serum which had growth-promoting activity. Hoffman, Dingwall, and Andrus (8) obtained an active protein fraction from an extract of sheep heart and Davidson and Waymouth (9) obtained active protein fractions from brain, heart, and skeletal muscle of sheep embryos.…”
Section: Introductionmentioning
confidence: 99%
“…Carrel [5], Doberauer [6], Schmitt and Beneke [15], Struck and Engelhardt [17], among others, were able to prove experimentally that the age of the animal plays an essential part in wound-healing. In granula tion tissue, just like any other tissue, there exist alterations in the anabolic and the catabolic processes according to the rate of growth.…”
Section: Discussionmentioning
confidence: 99%
“…A correlation of the various parameters to one another could not be established. The findings were discussed in relation to those found in the literature.C arrel [5], D oberauer [6], N issen [10] and Sc h in k [13] reported that the rate of the process of wound-healing is, in old age, slower than it is in younger years. Several methods have been described in the literature of how studies of age-dependent building of granulation tissue can be conducted [2,4,9,14], We found the method of Boucek and N oble [3] especially suitable for the purpose of our examination.…”
mentioning
confidence: 99%
“…Une sbrie d'expbriences sp6ciales a men6 Carrel A la conclusion que le facteur emp&c'hant aiigmente dam lc &rnm avec l'bge de l'animal. 8) Des experiences institii6es avec den serums h6terologues ont monk6 que l'age de l'animal produit la mCme augmentation de Saction empCchante qu'on constatait dans les serums homologum ; voila. pourquoi les fihroblastes de poule peuvent servir comme un r k c t i f qui r6vhle les altbations amenks par l'ilge, dans le serum d'autres animaux.…”
Section: Principes De Croissance Humoraux Tri~phones"unclassified